Case Report: Therapeutic Strategy With Delayed Debridement for Culture-Negative Invasive Group A Streptococcal Infections Diagnosed by Metagenomic Next-Generation Sequencing - He, Wenfang; Wu, Chenfang; Zhong, Yanjun; Li, Jinxiu; Wang, Guyi; Yu, Bo; Xu, Ping; Xiao, Yiwen; Tang, Tiantian (Frontiers in Public Health, 2022)
Streptococcal toxic shock syndrome (STSS) caused by group A streptococcus is a rare condition that rapidly developed to multiple organ failure even death. Therefore, prompt diagnosis, initiate appropriate antibiotics and other supportive treatments are critical. Here we reported a case of STSS caused by group A streptococcus infection. A healthy 39-year-old man presented a sudden pain in the left lower extremity, followed by a high fever (40.0 °C) with dizziness, nausea, and shortness of breath. Twenty-four hours before the visit, the patient showed anuria. The patient was then admitted to the intensive care unit. Blood examination revealed elevated levels of inflammatory markers and creatinine. He suffered from septic shock, dysfunction of coagulation, acute kidney dysfunction, acute respiratory distress syndrome, and acute liver function injury. The diagnosis was obtained through clinical manifestation and metagenomic next-generation sequencing (mNGS) drawn from the pustule and deep soft tissue (lower limb) samples while all bacterial cultures came back negative. The pustule mNGS report detected a total of 132 unique group A streptococcus sequence reads, representing 96.3% of microbial reads while the soft tissue mNGS report identified a total of 142474 unique group A streptococcus sequence reads, representing 100% of microbial reads. The patient was treated with aggressive fluid resuscitation, antibiotics comprising piperacillin/tazobactam and clindamycin, respiratory support, following the delayed surgical debridement. Intravenous immunoglobulin was also used for 5 days. On the fourteenth day after admission, he was transferred to the general ward for follow-up treatment. Our case highlighted, for the first time, the key role of mNGS in the early diagnosis of culture-negative invasive group A streptococcal infection. The case also suggested that clindamycin combined with beta-lactam antibiotics and adjunction of intravenous immunoglobulin therapy with delayed debridement performed well in the management of unstable STSS patients.